From the Behavioral Pharmacology of Beta-Carbolines to Seizures, Anxiety, and Memory - Patrice Venault; Georges Chapouthier (The Scientific World Journal)
A number of beta-carbolines are inverse agonists of the GABA-A receptor complex, acting on the benzodiazepine site. They show convulsive properties when administered at high doses, anxiogenic properties at moderate doses, and learning-enhancing effects at low doses. These data suggest a possible physiological relationship, through the GABA-A receptor channel, between memory processes, anxiety, and ultimately, in pathological states, epileptic seizures. This relationship seems to be confirmed partially by experiments on mouse strains selected for their resistance (BR) and sensitivity (BS) to a single convulsive dose of a beta-carboline. These two strains also show differences in anxiety and learning abilities. However, some opposite results found while observing the behavior of the two strains suggest that in addition to pharmacologically induced anxiety, there is spontaneous anxiety, no doubt involving other brain mechanisms.